2023
DOI: 10.1088/1361-6463/acf6d1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CF4 concentration on the discharge dynamics and reactive species distribution of atmospheric nanosecond pulsed He plasma jet

Huan Zhao,
Lijun Wang,
Jie Liu

Abstract: Based on a two dimensional (2D) self-consistent model, the effect of different CF4 concentrations on the discharge dynamics characteristics, F-containing species distribution and the distribution of the axial and radial ionization rates of He atmospheric pressure plasma jet (APPJ) has been investigated. In addition, the accuracy of the simulation is verified by comparing the experimental results. The ionization rate of He APPJ enhances with the increase of CF4 from 0 to 2% because of the Penning ionization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Researches shown that the addition of a small amount of O 2 will increase the ionization intensity and electron density in He APPJ and significantly increase the density of atomic fluorine (F) in He/CF 4 plasmas [19,20]. Moreover, it was found in our previous work [21,22] that the ionization rate of He/CF 4 APPJ was enhanced and the density of some RFS increased at a small amount of CF 4 . Therefore, selecting the appropriate O 2 content and studying the effect of O 2 additive on APPJ characteristics and RFS content in the interaction between He/CF 4 APPJ and dielectric surfaces at a small amount of CF 4 have become the focus of this paper.…”
Section: Introductionmentioning
confidence: 87%
“…Researches shown that the addition of a small amount of O 2 will increase the ionization intensity and electron density in He APPJ and significantly increase the density of atomic fluorine (F) in He/CF 4 plasmas [19,20]. Moreover, it was found in our previous work [21,22] that the ionization rate of He/CF 4 APPJ was enhanced and the density of some RFS increased at a small amount of CF 4 . Therefore, selecting the appropriate O 2 content and studying the effect of O 2 additive on APPJ characteristics and RFS content in the interaction between He/CF 4 APPJ and dielectric surfaces at a small amount of CF 4 have become the focus of this paper.…”
Section: Introductionmentioning
confidence: 87%